2007
DOI: 10.2987/8756-971x(2007)23[99:smofmd]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Monitoring of Floodwater Mosquito Dispersal in Osijek, Croatia

Abstract: This paper demonstrates the possibility of using geostatistics to monitor the dispersal of mosquitoes for mosquito control programs at the municipal level. The case study objective was to quantify the dispersal of floodwater mosquitoes from the natural marshland Kopacki rit into the city of Osijek, Croatia, and to analyze the main factors controlling it. Fifty thousand adult Aedes vexans, Ochlerotatus sticticus, and Ochlerotatus caspius mosquitoes were marked with a powdered fluorescent pigment and released fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…vexans can move to a distance up to 32 km from the breeding site (Brust 1980;Carpenter & LaCasse 1955;Headlee 1945;Sparks et al 1986). In a research on mosquito migration in the Osijek area, the species has been observed 7.7 km from the breeding site (Sudarić Bogojević et al 2007). This indicates that host-seeking females of Ae.…”
Section: Disscussionmentioning
confidence: 99%
See 2 more Smart Citations
“…vexans can move to a distance up to 32 km from the breeding site (Brust 1980;Carpenter & LaCasse 1955;Headlee 1945;Sparks et al 1986). In a research on mosquito migration in the Osijek area, the species has been observed 7.7 km from the breeding site (Sudarić Bogojević et al 2007). This indicates that host-seeking females of Ae.…”
Section: Disscussionmentioning
confidence: 99%
“…The same seasonal dynamics of the species was reported in Slavonski Brod in 2001 (Merdić et al 2003). Ochlerotatus sticticus is widespread and a nuisance mosquito that can fly up to 11.7 km from the breeding site (Sudarić Bogojević et al 2007). …”
Section: Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The floodplain area of Kopački rit is situated north-east of the city of Osijek in the Baranja region, in a triangle formed by the rivers Drava and Danube, and it is described in detail in a previous paper (Sudarić Bogojević et al 2007). The sampling was conducted in five different environments: flooded (5 stations), urban (8 stations), urban near water -Drava River (4), agricultural -crops or orchards (17 stations), and combinations of urban and agricultural habitats (6 stations).…”
Section: Introductionmentioning
confidence: 99%
“…The objective of the work was to study movement of floodwater mosquitoes from Kopački rit to Osijek, however, traps could not be set north of the marking site because of mine fields as a result of recent war activities. So it is unknown how many mosquitoes dispersed in these directions (Sudarić Bogojević et al 2007). Information about the dispersal of mosquitoes from their breeding sites is useful when defining boundaries of area to be treated with insecticides to prevent the annoyance caused by mosquitoes in neighbouring communities.…”
Section: Introductionmentioning
confidence: 99%